2016
DOI: 10.1080/09593330.2016.1254281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volatile fatty acids in anaerobic conditions on viability of helminth ova (Ascaris suum) in sanitization of municipal sludge

Abstract: The present work aimed at evaluating the effect of four different mixtures of diverse volatile fatty acids (VFAs) on the viability of helminth ova (Ascaris suum), under mesophilic (35°C) anaerobic conditions and at different incubation times, in order to reproduce the process of two-phase anaerobic digestion. The mixtures of VFAs contained acetic, propionic, butyric, valeric, and isovaleric acids, used at concentrations normally found in acidogenic anaerobic digesters. The four treatments all showed a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that carboxylic acids inhibit growth of many bacteria, and recent work has also investigated their toxicity to Ascaris eggs. In HFM, Ascaris lumbricoides eggs are considered the most-resistant pathogens to waste treatment processes due to the hydrophobicity of the innermost lipid layer of the egg. At a pH below the p K a (∼4.8), carboxylic acids exist primarily in the uncharged acid form, which is more hydrophobic than the corresponding conjugate base and able to cross the lipid layer. Butkus et al exposed Ascaris eggs to solutions of carboxylic acids for 20 h at 37 °C at different pH values and concluded that carboxylic acids were more effective when the pH was below the p K a of the acid and that carboxylic acids with longer carbon chains are more effective, likely due to the increased hydrophobicity of the chain .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that carboxylic acids inhibit growth of many bacteria, and recent work has also investigated their toxicity to Ascaris eggs. In HFM, Ascaris lumbricoides eggs are considered the most-resistant pathogens to waste treatment processes due to the hydrophobicity of the innermost lipid layer of the egg. At a pH below the p K a (∼4.8), carboxylic acids exist primarily in the uncharged acid form, which is more hydrophobic than the corresponding conjugate base and able to cross the lipid layer. Butkus et al exposed Ascaris eggs to solutions of carboxylic acids for 20 h at 37 °C at different pH values and concluded that carboxylic acids were more effective when the pH was below the p K a of the acid and that carboxylic acids with longer carbon chains are more effective, likely due to the increased hydrophobicity of the chain .…”
Section: Introductionmentioning
confidence: 99%
“…The work of Rojas-Oropeza et al (2016) covers the study of the influence of volatile fatty acids (VFA) of four different compounds on the viability of eggs of A. suum. The compounds included acetic, propionic, butyric, valeric, and isovaleric acids.…”
Section: Discussionmentioning
confidence: 99%
“…VFAs are naturally present in biosolids and may play an important role in pathogen inactivation. In particular, VFAs appear to be significant in the inactivation of Ascaris ova [38][39][40] and enteric bacteria [41][42][43]. However, it is also well documented that bacteria that infects the human gut are relatively tolerant against high concentrations of VFAs [44][45][46][47][48][49].…”
Section: Volatile Fatty Acidsmentioning
confidence: 99%